Impact of a PEO-based Interphase at the Negative Electrode of "Zero Excess" Lithium-Metal Batteries. Issue 11 (1st November 2022) - Geng, Katrin; Eisenmann, Tobias; Parmar, Rahul; Rezvani, Javad; Gunnella, Roberto; Amati, Matteo; Gregoratti, Luca; Stepien, Dominik; Diemant, Thomas; Bresser, Dominic
Abstract : "Zero-excess" lithium-metal batteries represent a very promising next-generation battery concept, enabling extremely high energy densities. However, lithium metal deposition is often non-uniform and accompanied by severe side reactions with the electrolyte, limiting Coulombic efficiency and, thus, energy density and cycle life. To address this issue, we introduced a thin polymer-based artificial interphase at the negative electrode. The influence of this interphase on the lithium deposition, and generally the reactions occurring at the negative electrode, was evaluated by galvanostatic stripping/plating tests and a thorough ex situ analysis via scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX), scanning photoemission microscopy (SPEM), and soft-X-ray absorption spectroscopy (soft-XAS). The results demonstrate that the introduction of such a polymer-based interlayer allows for more stable cycling and reduces dendritic lithium growth owing to the formation of a more homogeneous, thin, and fluorine-rich passivation layer.